Synthesis and Structural Determination of Novel Fluorinated Steroidal Spiro(pyrazolo[4,3-e][1,2,4]triazin-3′-yl) Derivatives as Affecting Enzymatic Agents - Bakhotmah, Dina; Abdel-Rahman, Reda (Letters in Organic Chemistry, 2017)
Background: Spiro(pyrazolo[4,3-e][1,2,4]triazin-3′-yl) derivatives are key building blocks of many pharmaceuticals, agrochemicals and biologically active compounds. Fluorinated compounds have a remarkable record in medicinal chemistry and provide lead compounds for therapeutic applications, the influence of fluorination on acidity, hydrogen-bonding and lipophilicity that affect compound absorption and distribution. Methods: Novel fluorinated steroidal spiro(pyrazolo[4,3-e](1,2,4)-triazin-3′-yl) derivatives have been synthesized and evaluated as effective enzymatic agents for cellobiase activity against some fungi. The synthesis achieved by a cyclocondensation of 3-(antipyrin-4-imino)steroids with hydrazine hydrate followed by fluorinated acylation and aroylation. Results: The synthesized compounds with different fluorine substituents were obtained in moderate to good yields (56-83%). Most of the compounds (5a, 6a, 5b, 6b) were found to be more active over control and other tested compounds and have also showed significant antibacterial and antifungal activity. Conclusion: A series of novel compounds with high activity are synthesized, showed excellent enzymatic effects on the tested fungi C. Thermophilum and T. Lanuginosus due to the presence of fluorine atoms or group on the ring. The synthesized compounds bearing trifluoro acetyl substituents were more effective than their p-fluorobenzoyl substituents for the same fungi. Thus, the synthesized compounds shall prove as future enzymatic effects drugs with further research.
Keywords: Cellobiase